2014
DOI: 10.1007/978-3-642-44955-0_14
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance in the Philippines and Switzerland―A Comparison of the Institutional Environment and Practices

Abstract: P a g e 1 o f 16 C o r p o r a t e G o v e r n a n c e i n t h e P h i l i p p i n e s a n d S w i t z e r l a n d -A C o m p a r i s o n o f E n v i r o n m e n t a n d P r a c t i c e s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…First, their boards have a mean ( M ) = 2.534 for IDs ( SD = 0.928, range = 1 to 9), less than the three recommended by the CG Code for PLC (SEC, 2016), and a M = 0.275 for the proportion of IDs on the board ( SD = 0.083, range = 0.083 to 0.818), again less than the one‐third recommended by the CG Code for PLC (SEC, 2016). dela Rama et al (2014, p. 367) have indicated that Asian (and Philippine) firms are strongly reluctant to have IDs on their board. Second, their boards have a M = 4.239 for NEDs ( SD = 2.139, range = 0 to 11) and a M = 0.436 for the proportion of NEDs on the board ( SD = 0.162, range = 0.000 to 0.800).…”
Section: Results and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…First, their boards have a mean ( M ) = 2.534 for IDs ( SD = 0.928, range = 1 to 9), less than the three recommended by the CG Code for PLC (SEC, 2016), and a M = 0.275 for the proportion of IDs on the board ( SD = 0.083, range = 0.083 to 0.818), again less than the one‐third recommended by the CG Code for PLC (SEC, 2016). dela Rama et al (2014, p. 367) have indicated that Asian (and Philippine) firms are strongly reluctant to have IDs on their board. Second, their boards have a M = 4.239 for NEDs ( SD = 2.139, range = 0 to 11) and a M = 0.436 for the proportion of NEDs on the board ( SD = 0.162, range = 0.000 to 0.800).…”
Section: Results and Analysismentioning
confidence: 99%
“…The Philippines is a developing country that has weak regulatory enforcement; concentrated corporate ownership, often within a family; and weak minority investor protection (dela Rama et al, 2014). Like other emerging countries, the Philippines must deal with institutional voids—weak institutions to support product, capital, and labor markets; misguided regulations; and inefficient judicial systems (Khanna & Palepu, 1997).…”
Section: Institutional Environment: the Philippinesmentioning
confidence: 99%
See 3 more Smart Citations